Enhancing the Performance of West Tripoli Power Plant Gas Turbine Unit using Absorption Chiller - Fahed Tayeb Montasser; Nuri Mohamed Eshoul (African Journal of Advanced Pure and Applied Sciences, 2024)
Thermodynamics plays a fundamental role in understanding and optimizing the performance of gas turbine power plants. As well known that the gas turbine power plants are sensitive to inlet air temperature, as it directly influences their eﬃciency and power output. Inlet cooling systems, therefore, emerge as critical components in enhancing gas turbine performance, particularly in regions with high ambient temperatures. This research study the significance of adding an absorption chiller system to the West Tripoli gas turbine power plant, a crucial energy infrastructure asset in Libya. The research explores the process of adding an absorption chiller into the plant’s operation, leveraging its ability to utilize waste heat from the gas turbines to operate the absorption chiller. The work performed in this paper is modeling and improving the performance of a single gas turbine unit used in the West Tripoli power plant using the IPSEpro software. Furthermore, an absorption chiller was modelled for stabilizing the gas turbine inlet conditions. The result indicates that by stabilizing the inlet air temperature, the absorption chiller eﬀectively enhances the gas turbine performance such as, eﬃciency, leading to a notable increase in power output. This improvement translates into significant economic benefits for the power plant and contributes to the overall stability of Libya’s electricity supply.